VIBROSIEVE DIAGNOSTICS OF ELECTROMAGNETIC EQUIPMENT - Bondarenko, B. M.; Morozov, H. L.; Razhonov, A. P. (Science and Transport Progress, 2010)
In the article one of variants of checking the operability of relay equipment for railway automation is examined with the use of method of noise diagnostics (an identification of noise signals on the basis of using the moments of density of probability distribution for random noise signals).